2017
DOI: 10.1016/j.toxicon.2017.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Noxious newts and their natural enemies: Experimental effects of tetrodotoxin exposure on trematode parasites and aquatic macroinvertebrates

Abstract: The dermal glands of many amphibian species secrete toxins or other noxious substances as a defense strategy against natural enemies. Newts in particular possess the potent neurotoxin tetrodotoxin (TTX), for which the highest concentrations are found in species within the genus Taricha. Adult Taricha are hypothesized to use TTX as a chemical defense against vertebrate predators such as garter snakes (Thamnophis spp.). However, less is known about how TTX functions to defend aquatic-developing newt larvae again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 83 publications
(105 reference statements)
1
13
0
Order By: Relevance
“…Consistent with these field‐based observations, Calhoun, Bucciarelli, Kats, Zimmer, and Johnson () recently showed that five species of trematodes exhibited dose‐dependent increases in mortality with exposure to TTX. By comparision, aquatic macroinvertebrates that frequently co‐occur wiht newts showed little response to exogenous TTX over the same time peroid (Calhoun et al, ). However, whether such effects extend to other parasite taxa, including nematodes, fungi and viruses, is unknown.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Consistent with these field‐based observations, Calhoun, Bucciarelli, Kats, Zimmer, and Johnson () recently showed that five species of trematodes exhibited dose‐dependent increases in mortality with exposure to TTX. By comparision, aquatic macroinvertebrates that frequently co‐occur wiht newts showed little response to exogenous TTX over the same time peroid (Calhoun et al, ). However, whether such effects extend to other parasite taxa, including nematodes, fungi and viruses, is unknown.…”
Section: Discussionsupporting
confidence: 57%
“…For instance, larval trematodes such as R. ondatrae that encyst in the skin were encountered in <2% of hosts, despite being common among larval newts and other amphibians that develop in these ponds (Johnson & Wilber, 2017). Consistent with these field-based observations, Calhoun, Bucciarelli, Kats, Zimmer, and Johnson (2017) recently showed that five species of trematodes exhibited dose-dependent increases in mortality with exposure to TTX.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…To the best of our knowledge, the period of maximum infectivity for Cephalogonimus sp. cercariae is unknown; however, their lifespan is generally >14 h (Calhoun et al ., 2017). Diplostomum spathaceum and Schistosoma mansoni both belong to the order Strigeatida, as does the unidentified strigeid-type cercaria used here, showing declines in infectivity after 6 and 5 h post-emergence, respectively (Olivier, 1966; Karvonen et al ., 2003).…”
Section: Methodsmentioning
confidence: 99%
“…At each pond, we randomly selected about 10 individuals per species for ranavirus screening (mean = 20 total amphibians per site, range = 1–84). We sampled metamorphic anurans (Gosner stage 25–32; Gosner, ) and late‐stage larval newts (2–4 T; Calhoun, Bucciarelli, Kats, Zimmer, & Johnson, ) to maintain similarity in life stages among species because we were unable to collect metamorphic newts. Therefore, we controlled for differences among life stages in our sampling and did not hypothesise these differences would influence our observed patterns.…”
Section: Methodsmentioning
confidence: 99%